Association between the place of abortion and post-abortion contraceptive adoption and continuation: the case of India. Issue 2 (1st January 2022) - Gaur, Kirti; Shukla, Ankita; Acharya, Rajib
Abstract: The unmet need for contraception is documented as a significant determinant of unintended pregnancies and high number of induced abortions. The period immediately after an abortion is recognised as a unique opportunity to offer contraceptive services. This paper explores the association between place of abortion and women's post-abortion contraceptive behaviour. The reproductive calendar data from the National Family Health Survey (NFHS-4) (2015–16) was used for this study. Multinomial logistic regression models were used to understand factors associated with post-abortion method choices. Single decrement life-tables were built to examine rates of contraceptive discontinuation and proportional hazard models were employed to examine probability and correlates of method discontinuation. About 20% of women who underwent an abortion adopted a contraceptive method by the end of one month following an abortion. The decision to choose methods like sterilisation or intrauterine contraceptive devices (IUCDs) was associated with the place of abortion, past contraceptive behaviour, number and sex of surviving children at the time of abortion, mass media exposure, and time of the abortion. Compared to women who underwent an abortion at private health facilities, women who sought abortion at public health facilities were more likely to choose permanent methods or IUCDs. Furthermore, women who opted for an IUCD were less likely to discontinue the method compared to those using short-acting modern methods. The lack of post-abortion contraceptive choices for women is evident in the low uptake of post-abortion contraceptives in private facilities and the predominant promotion of permanent methods and IUCDs in public health facilities.